Academic Ethics of Islamic Higher Education Institutions in the Digital Era - Edi Sundowo; Hasan Asari; Maulidah Hasnah Anas; Ade Lestari; Sopian Lubis (STAI Miftahul Ula Nganjuk, 2024)
This study investigates academic ethics within Islamic higher education institutions, focusing on the impacts of technological advancements on academic integrity. As digitalization reshapes the landscape of education and scientific research, it offers both opportunities and challenges, particularly in preserving ethical standards. Digital misuse can undermine ethical principles, contributing to issues such as academic dishonesty and misconduct in scientific work. This research employs a descriptive qualitative approach, including observations, interviews, and document analysis. Findings reveal that Islamic higher education institutions uphold academic ethics grounded in national laws, regulations, and mutual agreements. However, there is limited engagement in research and academic activities by faculty and students, though no major ethical violations, such as plagiarism, were observed in the studied institutions. Despite efforts to enforce ethics, the digital era poses ongoing challenges, emphasizing the need for stronger ethical reinforcement in scientific endeavors.